Exclusive and Non-Exclusive Breastfeeding among Stunted and Normal 6–9 Month-Old-Children in Jatinangor Subdistrict, Indonesia - Viramitha Kusnandi Rusmil; Tri Oktaviani Prahastuti; Dimas Erlangga Luftimas; Tisnasari Hafsah (Althea Medical Journal, 2019)
Background: Stunting has become a public health problem in Indonesia, with the prevalence of stunting is 37.2% nationally and 25.6% in West Java. One of the causes of stunting is malnutrition that may occur because of not giving exclusive breastfeeding on the first 1000 days of life (FDL). The purpose of this study was to determine whether there was difference between exclusive and non-exclusive breastfeeding among stunted and normal 6–9 month-old-children.